THE INFLUENCE OF RENAL FUNCTION ON EFFICACY AND SAFETY OF LUSEOGLIFOZIN ADDED TO EXISTING INTENSIVE INSULIN THERAPY - Aziz, Hazwani; Hussein, Zanariah (Journal of the ASEAN Federation of Endocrine Societies, 2022)
OBJECTIVES The primary objectives of this study were to determine the efficacy of luseoglifozin on reduction of blood glucose in different eGFR categories. The secondary objectives were to evaluate the changes in body weight, blood pressure, urine microalbumin and eGFR. METHODOLOGY This study is a multicenter, open-label, single arm, interventional cohort study. We assigned 105 type 2 diabetes patients on intensive insulin therapy. The patients were stratified to three groups according to baseline eGFR; normal/mild renal impairment group with eGFR >60 mL/ min, mild-moderate impairment group with eGFR 45 to 60 mL/min and moderate-severe impairment group with eGFR 30 to 45 mL/min. All patients were treated with luseoglifozin and followed up for 24 weeks. This research was approved by an ethical committee. RESULTS There was significant HbA1c reduction at week 24 from baseline in normal/mild renal impairment group with median changes of -0.7% (± 1.4)(p<0.001). Fasting plasma glucose demonstrated significant reduction in normal/ mild renal impairment group with mean difference of -1.69 mmol/L (-2.61, -0.77)(p<0.001) and in mild-moderate renal impairment group with mean difference of -1.69 mmol/L(-3.33,-0.06)(p 0.044). Body weight was significantly decreased in normal/mild renal impairment and mild- moderate renal impairment group with median change of -0.5 kg (±2.9)(p 0.011) and -0.75 kg (±2.0)(p 0.019) respectively. There was no significant change in blood pressure, urine microalbumin and eGFR. Hypoglycemia incidence was higher among patients in lower eGFR and all were mild hypoglycemia. CONCLUSION Significant improvement in glycaemic control and body weight reduction were observed after treatment with luseoglifozin, particularly in normal/mild renal impairment group.